Correction: Variation in the incidence of type 1 diabetes mellitus in children and adolescents by world region and country income group: A scoping review. - PLOS Global Public Health Staff (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0001099.].